Translating Intonational Meaning by Non-Intonational Means - Josipović, Višnja (1998)
The differences between English and Croatian illustrated in this paper have implications for translation/interpreting in both directions. In translation from English to Croatian one should consider inserting such non-intonational means as the emphatic dative pronoun, breathy voice and characteristic facial expression, to convey the intended meaning more adequately. Likewise, when translating from Croatian to English, one should be aware of the pragmatic function of such features and in oral interpretation try to express it using the right intonational patterns.
Projekt MZOS
ENG